Psychogenic polydipsia: A case of water intoxication (Indian Journal of Case Reports, 2025)
Psychogenic polydipsia (PPD), a clinical disorder characterized by polyuria and polydipsia, is a common occurrence in inpatients with psychiatric disorders. Primary polydipsia (PP) is a disorder that is clinically characterized by excessive thirst accompanied by increased fluid intake and subsequent excessive excretion of urine without an obvious cause. PP in adults is due to psychogenic causes, is a rare condition and may be more prevalent than thought. There is some evidence for pharmacological management of this condition, but nonpharmacological management, starting from psycho-education to behavioural modification therapy involving family members, can be a very effective strategy. This case report describes a 35-year-old male with schizophrenia who presented with confusion, seizures, and severe hyponatremia due to compulsive water consumption. Prompt diagnosis and management, including fluid restriction, careful sodium correction, and psychiatric intervention, led to symptom resolution. This case highlights the importance of early recognition and a multidisciplinary approach in preventing life-threatening complications associated with PPD. Further research is needed to establish standardized treatment guidelines.